2017
DOI: 10.1002/mc.22732
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations in transthyretin gene associated with hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the major health problems with increasing incidence worldwide. We report the elevation in transthyretin (TTR) expression following HCC induction using diethylnitrosamine (DEN) and 2-aminoacetylfluorine (2-AAF) in male Wistar rats. The increase in its expression took place at very early stage and remained elevated throughout HCC progression. The analysis of TTR gene in HCC bearing rats revealed four novel mutations that alter three amino acids at positions 61, 100, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
4
1
Order By: Relevance
“…Our result was similar to a finding of Liao et al, [17] who showed that cirrhotic patients with HCC had lower pre-albumin level. While in disagreement to result of Katare et al who observed that serum TTR level showed 4 times increase in HCC patients than in control [13].…”
Section: Disucssioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Our result was similar to a finding of Liao et al, [17] who showed that cirrhotic patients with HCC had lower pre-albumin level. While in disagreement to result of Katare et al who observed that serum TTR level showed 4 times increase in HCC patients than in control [13].…”
Section: Disucssioncontrasting
confidence: 77%
“…TTR is considered as a sensitive marker for the diagnosis of patients with liver cell damage, liver cirrhosis or hepatocellular carcinoma, reflecting the impaired liver synthetic function [12] . Katare et al [13] was the first to report that development of HCC is associated with increased level of serum TTR, where serum TTR level showed 4 times increase in HCC patients than in control. Therefore, detection of increased level of TTR alone or in combination with other validated markers may be potentially informative biomarker for detection of HCC at early noninvasive stage.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, hepatic Lpl, which supports clearance of blood triglyceride [17], Lrp1, which participates in uptake by liver of chylomicrons and very low-density lipoproteins from blood [18], and Acsl1, which activates long-chain fatty acids and facilitates lipid biosynthesis [19], were highly down-regulated (−90%, −87%, and −70%, respectively) in midnolin knockdown cells. Indeed, dysregulation of Aldh1a1 [20], Ttr [21], Rbp1 [22], Lpl [23], Lrp1 [24], and Acsl1 [25] in HCC has previously been reported. Given the important role of retinoic acid metabolism [26] and that of lipid metabolism [27] in regulating cell growth/transient amplification of cells and differentiation in cancer, we propose that midnolin knockdownmediated disruption of such metabolic pathways may explain the observed reduction in tumorigenic potential of midnolin knockdown cells in vitro and in mice.…”
Section: Midnolin Knockdown-mediated Disruption Of Retinoic Acid/lipi...mentioning
confidence: 89%
“…The differential expression of TTR had important biological significance in the development of cutaneous T-cell lymphoma ( 20 ). Katare et al found four mutations of TTR gene in LC rats, which changed three amino acids at positions 61, 100 and 115 ( 21 ). The mutation at position 115 interfered with the formation of TTR tetramer, leading to TTR accumulation ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Katare et al found four mutations of TTR gene in LC rats, which changed three amino acids at positions 61, 100 and 115 ( 21 ). The mutation at position 115 interfered with the formation of TTR tetramer, leading to TTR accumulation ( 21 ). With the deepening of TTR research, TTR could be used as a potential biomarker for pancreatic ductal adenocarcinoma ( 12 ).…”
Section: Discussionmentioning
confidence: 99%